Stapled hemorrhoidectomy: present status - Lacerda-Filho,Antônio (2005)
AIM: To evaluate cost-effectiveness of stapled hemorrhoidectomy comparing its results with conventional technique. SOURCE OF DATA: We retrospectively analyzed the MEDLINE data basis from 2000 to 2004 studying randomized clinical trials which compared pain intensity, recovery period, return to work and occurrence of anal incontinence, in addition to postoperative complications and costs evaluation between stapled and conventional hemorrhoidectomy during different periods of follow-up. CONCLUSIONS: Stapled hemorrhoidectomy provides lesser postoperative pain and earlier return to work than conventional hemorrhoidectomy. However, its efficacy could not be determined, since rigorous prospective and randomized clinical trials with long-term follow-up periods and large size samples are not available at this time.